Ancient Greco-Roman meters and stanzas in Russian poetry: origin and development - Mihhail Lotman (Studia Metrica et Poetica)
The basis of the metrical repertoire of Russian poetry is made up of meters of ancient Greco-Roman origin, which came through the intermediary of German poetry. The basic stanzaic models also originated from there. Meters and stanzas transplanted directly from the ancient tradition are quantitatively marginal but are important from the point of view of self-evaluation of culture.